Digitalization of Tourism Management through Tourism Information Systems and E-Ticketing to Enhance Efficiency and Competitiveness - Ari Muhardono; Wenti Ayu Sunarjo; Daru Anggara Murty; Pryamitra Agus Saputra (SISTEMASI, 2026)
This research aims to design and implement an integrated Tourism Information System and E-Ticketing platform for BUMDes Tirta Arum, to evaluate the effectiveness of an integrated digital system developed for tourism destinations managed by BUMDes. This study uses a Research and Development (R&D) approach using the System Development Life Cycle (SDLC) model, combined with a before-after quantitative evaluation framework to measure changes in operational performance indicators, including transaction processing time, reporting efficiency, error rate, service capacity, and digital visibility. The results show a significant improvement in performance after the implementation of the system. The average transaction processing time decreased by 83.33%, the reporting time increased by 91.67%, and the recording error rate decreased by 95%. In addition, daily transactions recorded increased by 66.67%, reflecting an increase in service capacity. From a digital marketing perspective, the website generated 15,000 impressions within three months with an average search ranking position of 8.9, indicating strong digital visibility, although a Click-through Rate of 0.8% indicates the need for further optimization to increase user engagement. These results highlight that the digitization-enabled automation of the system increases the efficiency, transparency, and competitiveness of the system and verifies that rural tourism digitalization is a digitally oriented upgrading in strategic institutional restructuring and not only the adoption of technology.